IMPLEMENTASI LESSON STUDY SEBAGAI SARANA MENUMBUHKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATAKULIAH MATEMATIKA DASAR - Martyana Prihaswati; Eko Andy p.; Sukestiarno Sukestiarno; Mulyono Mulyono (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Basic mathematics courses are one of the subjects taught in non-mathematics courses or majors where the majority of students tend to avoid math. Mathematical problem solving skills of non-math students tend to be low. Though problem-solving ability is the main reason to learn math. So it is necessary to improve learning with lesson study through the application of problem based learning with character education approach. This research uses qualitative approach with descriptive method of analysis. The conclusion of this study is the implementation of lesson study through the application of PBL learning with character education approach is in accordance with the stages of the lesson study, namely planning (plan), implementation (do), and reflection (see). These three stages can improve students' mathematical problem solving skills in basic mathematics courses. Need to improve the way of learning, learning methods, and the atmosphere of learning so that the ability of students more leverage. Keywords : problem solving, lesson study, basic mathematic